Menilai Perilaku Konsumtif Mahasiswa Atas Pengaruh Dari Kemudahan Penggunaan Mobile Banking - Jannah, Niswatul; Kuswati, Rini (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2024)
Most consumers now prefer shopping online rather than offline. Supported by easy access to shopping services such as Shopee, Tiktok Shop and Tokopedia, the online shopping trend is growing rapidly. Regarding the ease of shopping, the researchers decided to analyze the impact of the ease of using mobile banking on consumer behavior among FEB students. The research is based on a quantitative method which was distributed via a questionnaire with a rating scale of 1-5 to 220 active students of the economics and business faculty at Muhammadiyah University of Surakarta which was then processed via SPSS v20. The results found that there was a significant influence on the role of ease of use such as easy to learn, flexible, controllable, and easy to use on the consumptive behavior of FEB students.